THE INFLUENCE OF BRAND IMAGE, PRICE DISCOUN, PACKAGE BONUSES AND PRODUCT QUALITY ON BUYING IMPULSE IN ORIFLAME PRODUCTS - Cut Annisa Sabilla; Munandar; Syamsul Bahri; Jullimursyida (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to test of brand image, price discount, package bonuses, and product quality on impulse buying of Oriflame products. The data in this research was collected using questionnaires as the data collection instrument. The sample consisted of 130 respondents. This research used a quantitative approach with multiple linear regression analysis and was processed using SPSS (Statistical Package for the Social Sciences). The hypothesis was tested using SPSS version 26.0. The results of this study indicate that, partially, the brand image variable has a positive and significant effect on impulse buying of Oriflame products, statistically 0.002 < 0.05, and has a t-value > t-table value of 3.246 > 1.656. The price discount variable does not affect and is not significant for impulse buying of Oriflame products, statistically 0.947 > 0.05, and has a t-value < t-table value of 0.066 < 1.656. Meanwhile, the package bonuses variable has a positive and significant effect on impulse buying of Oriflame products, statistically 0.004 < 0.05, and has a t-value > t-table value of 2.974 > 1.656. Additionally, the product quality variable has a positive and significant effect on impulse buying of Oriflame products, statistically 0.000 < 0.05, and has a t-value > t-table value of 4.713 > 1.656. The Adjusted R Square value of the independent variables, namely brand image, price discount, package bonuses, and product quality, shows that 41.2% of the variance is explained by these variables, while the remaining 58.8% is explained by other variables not included in this study.